Perancangan Freeze Vacuum Drying Menggunakan Thermal Energy Storage untuk Mengeringkan Lidah Buaya dengan Kapasitas 4 kg - Martin, Awaludin; Cahyati, Wulan; Adriyandy, Warits; Mainil, Rahmat Iman (Universitas Muhammadiyah Metro, 2025)
Freeze vacuum drying is known as the best drying method in maintaining the nutritional quality and physical appearance of the product. However, this method has the disadvantages of a slow drying rate and high energy consumption. This study aims to improve the efficiency of the drying process by utilizing waste heat from the condenser using a thermal energy storage system using Phase Change Material (PCM) in the form of paraffin wax. This study uses a system design method that is continued to the testing stage with the results of the design of the tube diameter used, namely 0.00953 m, then the evaporator dimensions are obtained with a pipe length of 23 m, and the evaporator surface area is 7.13 x 10-5 m2. For the condenser, the pipe length is 15.9 m, and the condenser heat transfer area is 0.4762 m2. Energy consumption for drying 4 kg of aloe vera using Thermal Energy Storage (TES) is 8.937 kWh, with a design Coefficient of Performance (COP) value of 3.8 and an actual COP of 2.5.